2015
DOI: 10.1159/000376560
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Toxicity after Radiotherapy for Breast Cancer: Myths and Facts

Abstract: Radiotherapy is an important component in the multidisciplinary treatment of breast cancer. In recent years, the cardiac risks of radiation have been discussed several times. This problem has long been known and resolved from the radiotherapeutic point of view. The current data is briefly described here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Another promising technique for breast only RT is prone-positioned breast irradiation, especially in patients with large breasts [50]. This technique exploits gravity to elongate the treated breast away from the heart and lung.…”
Section: Modern Radiotherapy Techniques Heart Sparing Techniques In Bmentioning
confidence: 99%
“…Another promising technique for breast only RT is prone-positioned breast irradiation, especially in patients with large breasts [50]. This technique exploits gravity to elongate the treated breast away from the heart and lung.…”
Section: Modern Radiotherapy Techniques Heart Sparing Techniques In Bmentioning
confidence: 99%
“…Cardiac toxicity after breast cancer [16,34,48,52], lung cancer [53,54] and mediastinal lymphoma [49,50,59] is the most reported radiation-induced complication [51]. The common clinical complications are asymptomatic pericarditis, congestive heart failure, and heart infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Since most radiotherapy-associated cardiac side effects occur after 15 years or more, currently available results must be assessed with caution, especially in women with a long life expectancy and an unhealthy lifestyle. However, no significant cardiotoxicity has been observed in modern normofractionated radiotherapy for breast cancer with current radiotherapy techniques making it now safer than in the past [18]. Recently, Chan et al [19 ]reported a 15-year follow-up of cardiac injury, comparing hypofractionation versus normofractionation in left-sided early-stage breast cancer patients.…”
Section: Ongoing Controversies Concerning the Hypofractionated Treatmmentioning
confidence: 99%